Tin and iron co-doping strategy for developing active and stable oxygen reduction catalysts from SrCoO3−δ for operating below 800 °C - Chen, Y.; Qian, B.; Shao, Zongping (Elsevier, 2015)
SrCoO3−δ has long been a promising catalyst for the oxygen reduction reaction in solid oxide fuel cells (SOFCs). However, its rather unstable cubic phase structure greatly hinders its practical application. Stabilizing the simple cubic phase structure of SrCoO3−δ while preserving a suitable oxygen reduction activity is an important topic of research. Herein, we propose a Sn and Fe co-doping strategy for tuning the B-site of SrCoO3−δ to stabilize its oxygen vacancy-disordered cubic lattice structure at the operating temperatures of intermediate-temperature SOFCs (600–800 °C). Fe doping can greatly increase the solubility of Sn in SrCoO3−δ, which mainly acts as the dopant for cubic phase structure stabilization. Materials with a nominal composition of SrCo0.6(Fe0.4−xSnx)O3−δ (x = 0–0.15) are designed, and the solubility of Sn in SrCoO3−δ can reach x = 0.1. For the first time, we prepare a phase-pure Sn-doped and SrCoO3−δ-based cubic perovskite oxide of SrCo0.6(Fe0.3Sn0.1)O3−δ with long-term cubic structure stability. More importantly, the Sn doping does not harm the oxygen reduction activity of SrCo0.6Fe0.4O3−δ, and the electrode composed of SrCo0.6(Fe0.3Sn0.1)O3−δ possesses a low polarization resistance of ∼0.1 Ω cm2 at 600 °C. A 400-h-long stability test demonstrates that the SrCo0.6(Fe0.3Sn0.1)O3−δ material is a promising oxygen reduction catalyst for SOFCs.